THE TEACHERS' CLINIC. - Kaulback, Frank S.; Sharits, Earl C.; Braden, Andrew D.; Gulden, Douglas J.; Stokes, Charles J.; Lane, Joe; Davidson, Sidney (The Accounting Review, 1954)
Abstract The article presents devices and techniques developed by the member of accounting profession for the presentation of the knotty aspects of accounting. The first method presented focuses on the accounting problems related to business income and the cash basis. Money profits are basic to the management of a business. The cash basis, where properly applied, involves considerably more than receipts and disbursements. Accounting on the cash basis means that net income is determined by including income and gains actually or constructively received and deducting those expenses actually or constructively paid, losses sustained, and allowable depreciation or amortization for the period. Cash includes not only money but also commercial paper redeemable in money on demand such as money orders, bank drafts or checks. It does not include notes or similar promises to pay money at some future time. The general rule is that a bank check received constitutes an actual or conditional receipt, even though the holder refrains from depositing or cashing the check until a later date. Transactions near the end of the year call for decision as to the exact time receipt occurs.